2018
DOI: 10.3892/ol.2018.8955
|View full text |Cite
|
Sign up to set email alerts
|

Expression of AQP3 and AQP5 as a prognostic marker in triple‑negative breast cancer

Abstract: Triple-negative breast cancer (TNBC) is a common type of breast malignancy with high a propensity for metastasis and locoregional recurrence. The aim of the present study was to investigate the expression of aquaporin (AQP) 3 and AQP5, analyze their association with clinicopathological parameters and explore their clinical significance in tissue samples from patients with TNBC. Immunohistochemistry was performed to detect the expression patterns of AQP3 and AQP5 in 96 patients with TNBC who underwent surgery b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 29 publications
0
49
0
2
Order By: Relevance
“…In particular, we have shown that increased expression of AQP5 in the breast cancer cells was associated with cancer cell migration, metastasis, and poor prognosis in human patients . It was also reported that AQP3 and AQP5 abundance was notably increased in triple‐negative breast cancer patients . Moreover, a positive tendency in the correlation analysis between AQP5 and Rac‐GTP expression was reported in human breast cancer tissue, the latter being a GTPase involved in cell migration .…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…In particular, we have shown that increased expression of AQP5 in the breast cancer cells was associated with cancer cell migration, metastasis, and poor prognosis in human patients . It was also reported that AQP3 and AQP5 abundance was notably increased in triple‐negative breast cancer patients . Moreover, a positive tendency in the correlation analysis between AQP5 and Rac‐GTP expression was reported in human breast cancer tissue, the latter being a GTPase involved in cell migration .…”
Section: Introductionmentioning
confidence: 64%
“…13,14 It was also reported that AQP3 and AQP5 abundance was notably increased in triple-negative breast cancer patients. 15 Moreover, a positive tendency in the correlation analysis between AQP5 and Rac-GTP expression was reported in human breast cancer tissue, the latter being a GTPase involved in cell migration. 16 Also, AQP5 overexpression in normal epithelial cells (MDCK cells) stimulated cell detachment and dissemination from migrating cell sheets, which could be counteracted by inhibition of Ras.…”
Section: Introductionmentioning
confidence: 95%
“…Accumulated studies have shown that AQPs are involved in tumor metastasis [15]. AQP3 and AQP5 can be used as new markers for breast cancer [38]. Another study showed that overexpression of AQP3 in mammalian cells can promote cell proliferation efficiency and cell cycle transition [39].…”
Section: Discussionmentioning
confidence: 99%
“…Development of gastric adenocarcinomas is a stepwise progression of histologic lesions, starting with gastritis, followed by intestinal metaplasia, dysplasia, and eventually invasive adenocarcinoma. AQP3 has been reported to associate with human cancer progression and metastasis, such as pancreatic ductal adenocarcinoma, prostate cancer, cervical intraepithelial neoplasia, and triple-negative breast cancer [22][23][24][25][26]. However, the role of AQP3 and its expression pattern in gastric carcinogenesis remain unclear.…”
Section: Discussionmentioning
confidence: 99%